Code of ethical conduct and core competencies for medical educators: fostering integrity and excellence - Khadija Farrukh (Journal of the Pakistan Medical Association)
Ethics refers to a branch of philosophy that deals with the study of moral principles and values that directs individual and group behaviour. It is apprehensive to what is right and what is wrong under certain circumstance and in different situations. The code of ethics are the fundamental values that guides code of conduct.1 There is imperative need to develop code of ethics and code of conduct for medical educators in Pakistan. Code of ethics plays a guiding role to implement code of conduct. There should be some standards to set levels of acceptable medical educator performance. Performance benchmark should be created to assess level of competence in medical educators by defining core competencies1.